Enhancing Management Research through Qualitative Methods - Balbastre-Benavent, Francisco (2024)
Considering the changes and uncertainties of the current environment that affect management in organizations, the use of qualitative methods in business research facilitates the study of organizational phenomena from a different perspective while acknowledging their complexity. The objective of this special issue is to offer greater exposure to empirical studies that thoroughly employ qualitative methods to solving business and management problems. We have attempted to showcase how diverse  Qualitative methodologies, from classic case-based strategies to more novel ones such as action research, provide new visions for approaching the study of organizational realities. Also, we have briefly reflected on the application of new tools as visual techniques or AI to business and management research. Therefore, this special issue offers five papers that, from different methodological perspectives and content, seek to contribute to this objective. We hope that this special issue represents a significant advancement in the visibility and appreciation of qualitative methods within the field of business and management research.